Konstruksi Sosial dalam Toleransi Beragama di Kabupaten Timor Tengah Selatan - Marten Elia Bonsale; Nursalam; Zulkhaidar Abdussamad; Zainur Wula; Syarifuddin Darajad (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2026)
This study aims to analyze the social construction of religious tolerance in Maulum Village, East Amanuban District, South Central Timor Regency, East Nusa Tenggara. The research focuses on understanding how the community builds, maintains, and applies the values ​​of religious tolerance in daily life. This study uses a qualitative approach, a research method that focuses on understanding the meaning of a social phenomenon based on the experiences of individuals or groups. The results show that religious tolerance in Maulum Village is formed and developed through various social and cultural values ​​entrenched in the community, such as the spirit of mutual cooperation, social solidarity, a sense of family, and respect for differences in belief. These values ​​are reflected in various shared activities, including community activities, religious celebrations, and cooperation in addressing various social needs. Furthermore, the role of religious leaders, traditional leaders, and the village government contributes to strengthening harmonious relations between religious communities through open communication and mutual respect. This study concludes that religious tolerance in Maulum Village is not only a value held by individuals but has also become an integral part of the community's social life, manifested in various forms of daily interaction. This condition supports the creation of a harmonious, peaceful, and harmonious life amidst the religious diversity within the community.